Pengaruh Store Atmosphere, Bonus Pack, Dan Halal Awareness Terhadap Purchase Intention (Studi pada Store Retail Watsons Malang Town Square) - Febrianisa Safira Azzahra; Jeni Susyanti; Ita Athia (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study was motivated by the increasing competition in the health and beauty retail sector, which necessitates an understanding of the factors influencing consumer purchase intention, including shopping experience and halal awareness. The objective of this study is to analyze the influence of store atmosphere, bonus packs, and halal awareness on consumer purchase intent. The study employs a quantitative approach using a survey method involving 112 respondents selected via purposive sampling, with data analyzed using multiple linear regression. The results indicate that all three variables have a positive and significant influence on purchase intention, both partially and simultaneously, with halal awareness being the most dominant variable. This indicates that, in addition to promotional factors and store atmosphere, halal aspects are a primary consideration in shaping consumer purchase intentions. In conclusion, purchase intention can be increased through the management of an attractive store atmosphere, effective bonus pack strategies, and the strengthening of product halal guarantees. The implications of this study underscore the importance of integrating marketing strategies with consumers’ religious values to enhance retail competitiveness. Keywords: Store Atmosphere, Bonus Pack, Halal Awareness, Purchase Intention